Role of free tissue transfer in management of chronic venous ulcer - K. Murali Mohan Reddy; D. Mukunda Reddy (Indian Journal of Plastic Surgery, 2004)
Most of the venous ulcers will heal with the treatment of primary venous problem. But a few patients will have refractory, recurrent chronic venous ulcers causing inconvenience to the patients in terms of loss of productive working hours. There is no standard method available for treatment of this chronic problem. Our modality of treatment includes wide excision of ulcer, ligation of incompetent perforators and coverage of defect with well vascularized tissue by free tissue transfer. We have analyzed this form of treatment in five patients with satisfactory result.